(untitled) (Current Horticulture, 2024)
Multiple cropping is the best way of sustainable intensification of crop production, from the limited resources. More flexibility in planting and harvesting of tropical root and tuber crops provide ample scope for various crop production systems. Intercropping of legumes, cereals, and vegetables in root and tuber crops increased system productivity with land-use efficiency, though yields of sole crop ofroots and tubers decreased. Intercropping root and tuber crops in plantation and fruit tree crops gave additional returns. Weed suppression, pest and disease reduction and improvement in soil nutrient status are the additional benefits of root and tuber crops involved in multiple cropping systems. In rice (Oryza sativa L.)-based cropping system in the coastal plains of Odisha, West Bengal, Karnataka, Tamil Nadu and Andhra Pradesh, sweet potato (Ipomoea batatas L. Lam.) is planted after harvesting of rice to take advantage of the residual soil moisture and fertilizers. Multiple cropping also reduces severity of pests and diseases. The climate smart root and tuber crops generate assured income under various cropping systems.